SIMULASI PENDULUM TERBALIK (INVERTED PENDULUM) PADA SEBUAH KERETA MENGGUNAKAN BAHASA PEMROGRAMAN MATLAB 7.5 - Aditya Prapanca, ; Noor Anita Candra Dewi, (Matematika dan Sains, 2010)
Hanger or pendulum form a thing which to adhere at pivot cart and can to be move with one level freedom (in the same direction or the contrary direction with hand of clock). In principle the inverted pendulum system form which which the characteristic system not stable or non-linear and physical system to do from pendulum, horse-drawn cart or cart and motor DC. The direction from research to conduct is strive for in order that pole inverted pendulum mentioned in order that constant in proportion at inverted position. Because of that, for control the non-linear system to be needed a certain model mathematical which the decrease from relationship fisis system with the conduct vicinity equation movement Lagrange and too conduct linearisasi to be able linear system. The results of this research the obtain that with using method above obvious not yet can result optimal. That is more great alteration mass pendulum, cart and pendulum movement to right with the angle of pendulum speed which stable decrease at inverted position. Whereas at the moment is more great alteration length pendulum, cart and pendulum movement to right with the angle of pendulum speed which stable enough at inverted position.